Pemberdayaan Ekonomi Keluarga Melalui Diversifikasi Produk Olahan dari Nanas - aiyub; aiyub, aiyub; Novitayani, Sri; Ramli, Farah Dineva (JURNAL PENGABDIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (JP3L), 2023)
In Indonesia, the pineapple (Ananas comosus L.) is a well-liked fruit. Kayukul is a village in Central Aceh that is well-known for being a pineapple-growing hub. However, farmers sell their harvest as fresh fruit. As a result, the price of pineapples reduces significantly during the rainy season and when the harvest is plentiful. Therefore, the diversification program offered in the Product-Based Community Services Program (PBCSP) to cultivate pineapples into meals and fresh drinks received positive responses from communities. This community service's goal is to increase the knowledge and skills of the local communities on how to transform pineapples into goods with added value, which they can then utilize as businesses to raise their family income. PBCSP was conducted in three steps, namely preparation, implementation, and evaluation. The target group of PBCSP were teenagers, housewives, and micro, small, and medium business actors. PBCSP activities were carried out for a month with three feature products, namely: cookies, syrup, and jelly candy made from pineapple. Training on how to create the products was used to socialize the featured products with the target audiences. A participatory paradigm was used in the preparation, formulation, and evaluation of the products. The target groups' complaints and recommendations regarding the products served as guidance for product development. To boost the added value of products, the selection and the determination of product names (brands) and package development were made. It is hoped that PBCSP will be implemented in a sustainable manner because the evaluation results indicated that the communities thought the program was highly useful. In order to help the target groups who have acquired the knowledge and skills to produce the feature products offered, the government is also expected to offer business financing assistance to create diverse enterprises to raise their family income. Keywords: Community Services, Pineapple, Diversification, Pineapple cookies, Pineapple Syrup, Pineapple Jelly Candy